The Association Between Occupational Noise Exposure And The Incidence Of Hypertension Among Industrial Workers - Az Zahro, Putri Rahmawati; Onny Setiani; Yusniar Hanani Darundiati (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2025)
One common form of pollution is noise exposure, which, when exceeding the threshold of 85 dB(A), may increase the risk of hypertension. Hypertension is defined as systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg, with several risk factors including age, length of employment, smoking habits, sleep duration, obesity, and diabetes. This study aimed to analyze the risk factors of hypertension among workers in the wood furniture industry. An observational analytic study with a cross-sectional approach was conducted involving 100 male workers selected through purposive sampling. Statistical analysis was performed using the chi-square test. The highest measured noise intensity was 95.3 dB(A), with an average of 87.3 dB(A). The mean systolic and diastolic blood pressures were 127.5 mmHg and 82 mmHg, respectively. Bivariate analysis showed that noise intensity (p = 0.021; PR = 3.619) and obesity (p = 0.005; PR = 4.334) were significantly associated with the incidence of hypertension. It can be concluded that high noise exposure and obesity are risk factors for hypertension among wood furniture industry workers.